Dating and relationship violence victimization and perpetration among 11–16 year olds in Wales: a cross-sectional analysis of the School Health Research Network (SHRN) survey. (29th August 2019) - Young, Honor; Long, Sara Jayne; Melendez-Torres, G J; Kim, Hyun Sue; Hewitt, Gillian; Murphy, Simon; Moore, Graham F
Abstract: Background: This study examines the prevalence of dating and relationship violence (DRV) victimization, perpetration and joint victimization and perpetration, and associations between DRV and socio-demographic characteristics. Methods: Cross-sectional self-report data from 74 908 students aged 11–16 from 193 schools across Wales were collected and analysed using generalized estimating equations to examine prevalence and predictors of emotional and physical DRV victimization, perpetration and joint victimization and perpetration. Results: More girls reported emotional victimization (28%) and perpetration (18%) than boys (20% and 16%, respectively). More girls (8%) than boys (7%) reported physical perpetration. However, boys (17%) reported more physical victimization than girls (12%). Age-related trajectories of DRV victimization and perpetration were stronger in girls than in boys. Students from single or step parent homes, those in care, and certain ethnic minority groups had increased odds of DRV. No association was found between socioeconomic status and DRV. Conclusions: Age-related trajectories and the lack of social patterning by socioeconomic status point to the value of early, universal interventions, while some evidence of ethnic patterning and family structure-related risk factors suggest areas for further research and targeted interventions. DRV continues to be a major public health problem for which little UK-specific intervention evidence exists.